Keefektifan Ice Breaking dalam Mengembalikan Fokus dan Motivasi Belajar Siswa Kelas V di SD Negeri 004 Pulau Payung - Rahmad Danil (Universitas Muhammadiyah Enrekang, 2023)
Ice Breaking is a simple activity designed to change the atmosphere in a learning environment from dull, rigid, and drowsy to one that is active, enthusiastic, and spirited. It is meant to build an engaging and vibrant learning atmosphere. This research aims to investigate the influence of Ice Breaking in rekindling the focus of 5th-grade students at Public Elementary School 004 on Pulau Payung. The research employs a qualitative approach, specifically a descriptive-qualitative study. The instrument used for this research is a questionnaire. Data collection was conducted by distributing the questionnaire directly to the elementary school students. In this research, data analysis employed a four-category Likert scale, which included